The Effectiveness of ETLE Management of the Gakkum Satlantas Unit of the Jombang Police in Actioning Traffic Violations in Order to Realize Kamseltibcarlantas - Krisna, Anak Agung Rama Nanda (Indonesian Journal of Police Studies, 2024)
The high number of traffic violations in Jombang Regency interferes with safe and orderly traffic. ETLE (Electronic Traffic Law Enforcement) was introduced by the Indonesian National Police to facilitate and enhance traffic police actions in enforcing traffic violations. However, the management and socialization efforts by the Traffic Law Enforcement Unit of the Jombang Police Resort have not resulted in a decrease in the number of traffic violations in the Jombang Regency. The purpose of this research is to describe the management and effectiveness management of the ETLE by the Traffic Law Enforcement Unit of the Jombang Police Resort in enforcing traffic violations to achieve safe and orderly traffic. This research uses a qualitative approach with a field research type. The research location at the Jombang Police Resort as well as data sources used primary and secondary data sources. Data collection techniques include interviews, observations, and document studies. Data validity is ensured through triangulation. Data analysis techniques include data reduction, data presentation, and conclusion drawing. The conceptual literature of this research consists of organizational resource theory, effectiveness theory, traffic violations concept, ETLE concept, safe and orderly traffic concept, and Police Operational Guidelines (POG). The results show that the management of ETLE in enforcing traffic violations is said to not yet meet management standards. For the human resources aspect, it meets the criteria, budget allocations have been provided for unit needs, many facilities and infrastructure are still in need of repair, and the method of sending ETLE confirmation letters lacks clarity. The implementation of electronic traffic violation enforcement (ETLE) in realizing safe and orderly traffic in the Jombang Regency has not achieved a high level of effectiveness.